Marketing Analysis Of Chili Peppers (Capsicum Frutescens L) In The Aimas District Of Sorong Regency - aci aprianto; Aldila Mawanti Athirah; Anggita Ekaningtyas Hermawan (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: The purpose of this study is to analyze the marketing system, marketing margin, and distribution channel efficiency of cayenne pepper in order to provide recommendations for increasing farmers' income. Methodology: This study used descriptive quantitative method with quota sampling technique for 30 farmers from three sub-districts in Aimas District, and snowball sampling for marketing actors. Primary data were collected through observation, interviews, and questionnaires, while secondary data were obtained from relevant institutions. Data analysis was conducted by calculating marketing margins and Farmer's Share to assess marketing efficiency. Results: The results showed that there are three marketing channels for cayenne pepper, with the highest profit margin obtained from the direct channel (farmer-consumer) of Rp15,000/kg, followed by the channel through intermediary traders (Rp10,000/kg), and the channel through retailers (Rp5,000/kg). Findings: However, marketing efficiency is still low due to limited agribusiness knowledge, lack of access to finance, and lack of knowledge of the market. Novelty: This study recommends strengthening farmer capacity in terms of agribusiness management, simplifying distribution channels, and supporting infrastructure and fair marketing policies to improve the sustainability of cayenne pepper farming in Aimas District. Conclusion: There are three cayenne pepper marketing channels, with the highest profit margins obtained from the direct channel (farmer-consumer), followed by channels through collectors, and channels through retailers. However, marketing efficiency is still low due to limited agribusiness knowledge, limited market access, and high distribution costs.Type of Paper: research article.